Dialogical constitutionalism manifestations in the Brazilian judicial review - Valle, Vanice Regina Lírio do (Revista de Investigações Constitucionais, 2014)
The exponential growth in judicial review in Brazil, compared with the international scenery, is not out of tune – and it has a direct relation with many Brazilian constitutional features. An analytical text (with over 400 articles) and a large spectrum of fundamental rights, provide an ambience that favors highly intense controversy about State obligations in providing goods and public services, or even about the possible tensions that may arise between those same rights. The Brazilian Supreme Court faces that unmanageable number of lawsuits, notably related with claims regarding the non-granting of socioeconomic rights. That scenery is leading the Brazilian Supreme Court to some kind of experimentalism in the designing of its own rulings, applying techniques that can be easily associated with many manifestations of the so-called dialogical constitutionalism. All those experiences reveal that granting socioeconomic rights as a distributive justice goal requires a dialogic strategy in judicial review, in order to provide progressive implementation, preventing inequality. Still, those dialogic provisions face serious obstacles related with the menace of a merely symbolic use by the Judiciary and with a path of substitutive deliberation again by the Judiciary leading to reinforce Legislative inertia, social alienation from the debate and undermining democratic accountability. Adopting a dialogical constitutionalism model in Brazil might be a proper solution to allow its system to reach the functional development of the constitution’s goals – but it requires a deeper theoretical reflection.